Product Development Strategies to Create Marketing Sustainability in Multinational Pharmaceutical Companies - Wijayanti, Sari; Kusuma, Triana Hasty; Poluan, Stevi Jimry; Nisa, Rizka Fatkhin (AKSIOMA : Jurnal Manajemen, 2025)
The purpose of this research is to find out how product development strategies contribute to creating marketing sustainability in multinational pharmaceutical companies. This study was conducted using a qualitative approach (case study) using two key informants, namely a Country Medical Affairs Head and Product Manager from a multinational pharmaceutical company ‘X’ in Indonesia, and conducted in-depth interviews, data triangulation, and secondary data collection. The result of this study is the existence of clinical and commercial development in multinational pharmaceutical companies to create marketing sustainability by emphasizing strategy evaluation and product sustainability.
Keywords: Product Development; Multinational Pharmaceutical Company; Marketing Sustainability